2019
DOI: 10.1016/j.disc.2018.09.034
|View full text |Cite
|
Sign up to set email alerts
|

On the classification of linear complementary dual codes

Abstract: We give a complete classification of binary linear complementary dual codes of lengths up to 13 and ternary linear complementary dual codes of lengths up to 10.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 8 publications
0
39
0
Order By: Relevance
“…We denote by C(a 0 , a 1 , a 2 , a 3 , a 4 , a 5 ) the code whose generator matrix is G(a 0 , a 1 , a 2 , a 3 , a 4 , a 5 ). By the same argument as in [1], we obtain the following lemma.…”
Section: Classification Methodsmentioning
confidence: 83%
“…We denote by C(a 0 , a 1 , a 2 , a 3 , a 4 , a 5 ) the code whose generator matrix is G(a 0 , a 1 , a 2 , a 3 , a 4 , a 5 ). By the same argument as in [1], we obtain the following lemma.…”
Section: Classification Methodsmentioning
confidence: 83%
“…0, 0, 1) 2 (0, 0, 1, 0) 3 (0, 0, 1, 1) 4 (0, 0, 1, 2) 5 (0, 1, 0, 0) 6 (0, 1, 0, 1) 7 (0, 1, 0, 2) 8 (0, 1, 1, 0) 9 (0, 1, 1, 1) 10 (0, 1, 1, 2) 11 (0, 1, 2, 0) 12 (0, 1, 2, 1) 13 (0, 1, 2, 2) 14 (1, 0, 0, 0) 15 (1, 0, 0, 1) 16 (1, 0, 0, 2) 17 (1, 0, 1, 0) 18 (1, 0, 1, 1) 19 (1, 0, 1, 2) 20 (1, 0, 2, 0) 21 (1, 0, 2, 1) 22 (1, 0, 2, 2) 23 (1, 1, 0, 0) 24 (1, 1, 0, 1) 25 (1, 1, 0, 2) 26 (1, 1, 1, 0) 27 (1, 1, 1, 1) 28 (1, 1, 1, 2) 29 (1, 1, 2, 0) 30 (1, 1, 2, 1) 31 (1, 1, 2, 2) 32 (1, 2, 0, 0) 33 (1, 2, 0, 1) 34 (1, 2, 0, 2) 35 (1, 2, 1, 0) 36 (1, 2, 1, 1) 37 (1, 2, 1, 2) 38 (1, 2, 2, 0) 39 (1, 2, 2, 1) 40 (1,2,2,2) By the method given in Section 2.1, our exhaustive computer search completes the classification of (unrestricted) ternary [n, 4, d] codes for The unique code D 27 is not LCD.…”
Section: Results On D 3 (N 4)mentioning
confidence: 99%
“…In [1], the classification of ternary LCD [n, k] codes was done for n ≤ 10. To test equivalence of ternary codes by a program in the language C, the method given in [1] is also used in this note.…”
Section: Classification Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In their work, they presented several constructions of LCD codes and showed that non-binary LCD codes in characteristic 2 can be transformed into binary LCD codes by expansion. For further recent research on the topic we refer the reader to [2,12,15,28]. One of our main challenges is to construct LCD codes over finite fields that also have good error correcting properties.…”
Section: Introductionmentioning
confidence: 99%